The effect of ionization of spray on the wetting characteristics of an adiabatically cooled heat exchanger - Esterhuyse, Bernard de Waal (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScIng)--University of Stellenbosch, 2004.